Pengaruh kompres aloe vera terhadap pembengkakan payudara pada ibu post partum - Puspitasari, Vimala; Yuliana, Dewi; Nela, Ari Sukma (JOURNAL OF Qualitative Health Research & Case Studies Reports, 2025)
Background: Postpartum is the period that begins after the placenta is delivered until the uterus returns to normal as before pregnancy. Problems that often arise in the breasts of postpartum mothers are sore and sore nipples, swollen breasts, and mastitis or breast abscesses. Swollen breasts that press on the milk ducts will result in the baby not getting milk. Purpose: To find out whether aloe vera compresses have an effect on breast swelling in postpartum mothers. Methods: Quantitative research and the design used is quasi-experimental with one group pretest and posttest approach. The sample in the study were postpartum mothers who experienced breast swelling in the Gantiwarno Health Center Working Area on January 12-February 18 as many as 13 people using accidental sampling. Data analysis used univariate and bivariate analysis to identify the influence of each variable. Results: The mean value of the breast swelling scale before aloe vera compress was given to postpartum mothers was 5.31 with a minimum value of 4 and a maximum of 6. In addition, the mean value of the breast swelling scale after aloe vera compress was given to postpartum mothers was 4.00 with a minimum value of 2 and a maximum of 5. The non-parametric statistical test, namely the Wilcoxon test, showed that (p = 0.002) or <0.05, meaning that there was an effect of aloe vera compress on breast swelling in postpartum mothers. Conclusion: There is an effect of aloe vera compresses on breast swelling in postpartum mothers.   Keywords: Aloe Vera; Breast Engorgement; Post Partum.   Pendahuluan: Post partum merupakan masa yang dimulai setelah lahirnya plasenta sampai kondisi rahim kembali normal seperti saat sebelum hamil. Masalah yang sering timbul pada payudara ibu nifas yaitu puting susu nyeri dan lecet, payudara bengkak, dan mastitis atau abses payudara. Payudara yang bengkak dan menekan saluran air susu akan mengakibatkan bayi tidak mendapatkan air susu. Tujuan: Untuk mengetahui apakah pengaruh kompres aloe vera terhadap pembengkakan payudara pada ibu post partum. Metode: Penelitian kuantitatif dan desain yang digunakan adalah quasi eksperimen dengan pendekatan one group pretest and posttest. Sampel dalam penelitian adalah ibu postpartum yang mengalami pembengkakan payudara di Wilayah Kerja Puskesmas Gantiwarno pada 12 Januari-18 Februari sebanyak 13 orang dengan menggunakan accidental sampling. Analisis data menggunakan analisis univariat dan bivariat untuk mengidentifikasi pengaruh dari masing-masing variabel. Hasil: Nilai rata-rata (mean) skala pembengkakan payudara sebelum diberikan kompres aloe vera pada ibu post partum adalah 5.31 dengan nilai minimum 4 dan maximum 6. Selain itu, nilai rata-rata (mean) skala pembengkakan payudara sesudah diberikan kompres aloe vera pada ibu post partum adalah 4.00 dengan nilai minimum 2 dan maximum 5. Uji statistic non parametric yaitu uji Wilcoxon yang menunjukkan bahwa (p= 0,002) atau <0,05, artinya ada pengaruh kompres aloe vera terhadap pembengkakan payudara pada ibu post partum. Simpulan: Ada pengaruh kompres aloe vera terhadap pembengkakan payudara pada ibu post partum.   Kata Kunci: Aloe Vera; Pembengkakan Payudara; Post Partum.